Postoperative Adjuvant Therapy Benefits Non‐pCR Patients Rather Than pCR Patients for Locally Advanced ESCC: A Multicenter Real‐World Study - Defeng Liu; Ao Liu; Longxiang Guo; Yi Li; Yuanlin Li; Yuxiang Chi; Haiqun Lin; Jinming Yu; Minghuan Li (Thoracic Cancer)
ABSTRACT Background There is no unified standard in adjuvant therapy (AT) for patients with esophageal squamous cell carcinoma (ESCC) after neoadjuvant therapy and surgery. We evaluated the significance of AT for these patients and explored its influencing factors. Methods ESCC patients who underwent neoadjuvant therapy and surgery from 2019 to 2022 at three centers were divided into AT (n = 227) and non‐AT groups (n = 435). Baseline characteristics were balanced using propensity score matching (PSM). Primary endpoints were disease‐free survival (DFS) and overall survival (OS), assessed using the Kaplan–Meier method. Subgroup analyses and univariate and multivariate Cox regression analyses were conducted to identify the prognostic factors. Results The median follow‐up period is 36 (2–72) months. After PSM, the total population had 1‐, 2‐, and 3‐year OS rates of 71.3%, 66.0%, and 64.1%, respectively. There were no statistically significant differences in DFS (HR: 0.79; 95% CI: 0.55–1.14, p = 0.21) or OS (HR: 0.75; 95% CI: 0.49–1.13, p = 0.17) between AT and non‐AT groups. Subgroup analysis revealed that non‐pCR patients benefited from AT in DFS (p = 0.042) and OS (p = 0.033). Moreover, in non‐pCR patients who received AT, BMI ≥ 21.5 kg/m2 and ypN0 were independent protective factors of DFS. ypN0 was an independent protective factor of OS. In terms of AT regimens, the Kaplan–Meier analysis revealed that adjuvant immunochemotherapy (AICT) provided superior survival benefits than adjuvant radiotherapy and adjuvant chemotherapy. Conclusions Postoperative AT benefited ESCC patients with non‐pCR, while AICT may be a relatively better AT regimen in real‐world data, which deserves further exploration.